DISEMINASI KOMUNIKASI POLITIK ISLAM DAN DAKWAH ERA KONVERGENSI MEDIA DIGITAL - Muhammad, Firdaus; Irwan, (Jurnal Dakwah Tabligh, 2023)
The dissemination of Islamic political communication has accelerated with the presence of digital media. The public quickly received information about various political events with various issues that accompanied them. The issue of populism, radicalism in the name of religion, and marginalization of clerics to identity politics is part of the conversation as an effect of access to digital media, including social media. The acceleration and openness of access to political news is the impact of media convergence. Media convergence occurs when the boundaries between various media disappear, eventually forming a single media. The convergence of media changes all elements of information into digital form. Religious phenomena expressed in the digital space, this study uses the concept of da'wah and cyber media as perspective choices, the aim is to answer the problem of how cyber da'wah activism is carried out by religious communities amid the convergence of digital media. So it can be concluded that cyber da'wah activism, in addition to calling for goodness and preventing evil, turns out that in its da'wah display it also illustrates other interests such as political and ideological interests hidden behind da'wah messages displayed through digital media.